The following is a list of integrals (antiderivative functions) of logarithmic functions. For a complete list of integral functions, see list of integrals.

Note: x > 0 is assumed throughout this article, and the constant of integration is omitted for simplicity.

## Integrals involving only logarithmic functions

${\displaystyle \int \log _{a}x\,dx=x\log _{a}x-{\frac {x}{\ln a))={\frac {x\ln x-x}{\ln a))}$
${\displaystyle \int \ln(ax)\,dx=x\ln(ax)-x}$
${\displaystyle \int \ln(ax+b)\,dx={\frac {(ax+b)\ln(ax+b)-(ax+b)}{a))}$
${\displaystyle \int (\ln x)^{2}\,dx=x(\ln x)^{2}-2x\ln x+2x}$
${\displaystyle \int (\ln x)^{n}\,dx=x\sum _{k=0}^{n}(-1)^{n-k}{\frac {n!}{k!))(\ln x)^{k))$
${\displaystyle \int {\frac {dx}{\ln x))=\ln |\ln x|+\ln x+\sum _{k=2}^{\infty }{\frac {(\ln x)^{k)){k\cdot k!))}$
${\displaystyle \int {\frac {dx}{\ln x))=\operatorname {li} (x)}$, the logarithmic integral.
${\displaystyle \int {\frac {dx}{(\ln x)^{n))}=-{\frac {x}{(n-1)(\ln x)^{n-1))}+{\frac {1}{n-1))\int {\frac {dx}{(\ln x)^{n-1))}\qquad {\mbox{(for ))n\neq 1{\mbox{)))}$
${\displaystyle \int \ln f(x)\,dx=x\ln f(x)-\int x{\frac {f'(x)}{f(x)))\,dx\qquad {\mbox{(for differentiable ))f(x)>0{\mbox{)))}$

## Integrals involving logarithmic and power functions

${\displaystyle \int x^{m}\ln x\,dx=x^{m+1}\left({\frac {\ln x}{m+1))-{\frac {1}{(m+1)^{2))}\right)\qquad {\mbox{(for ))m\neq -1{\mbox{)))}$
${\displaystyle \int x^{m}(\ln x)^{n}\,dx={\frac {x^{m+1}(\ln x)^{n)){m+1))-{\frac {n}{m+1))\int x^{m}(\ln x)^{n-1}dx\qquad {\mbox{(for ))m\neq -1{\mbox{)))}$
${\displaystyle \int {\frac {(\ln x)^{n}\,dx}{x))={\frac {(\ln x)^{n+1)){n+1))\qquad {\mbox{(for ))n\neq -1{\mbox{)))}$
${\displaystyle \int {\frac {\ln x\,dx}{x^{m))}=-{\frac {\ln x}{(m-1)x^{m-1))}-{\frac {1}{(m-1)^{2}x^{m-1))}\qquad {\mbox{(for ))m\neq 1{\mbox{)))}$
${\displaystyle \int {\frac {(\ln x)^{n}\,dx}{x^{m))}=-{\frac {(\ln x)^{n)){(m-1)x^{m-1))}+{\frac {n}{m-1))\int {\frac {(\ln x)^{n-1}dx}{x^{m))}\qquad {\mbox{(for ))m\neq 1{\mbox{)))}$
${\displaystyle \int {\frac {x^{m}\,dx}{(\ln x)^{n))}=-{\frac {x^{m+1)){(n-1)(\ln x)^{n-1))}+{\frac {m+1}{n-1))\int {\frac {x^{m}dx}{(\ln x)^{n-1))}\qquad {\mbox{(for ))n\neq 1{\mbox{)))}$
${\displaystyle \int {\frac {dx}{x\ln x))=\ln \left|\ln x\right|}$
${\displaystyle \int {\frac {dx}{x\ln x\ln \ln x))=\ln \left|\ln \left|\ln x\right|\right|}$, etc.
${\displaystyle \int {\frac {dx}{x\ln \ln x))=\operatorname {li} (\ln x)}$
${\displaystyle \int {\frac {dx}{x^{n}\ln x))=\ln \left|\ln x\right|+\sum _{k=1}^{\infty }(-1)^{k}{\frac {(n-1)^{k}(\ln x)^{k)){k\cdot k!))}$
${\displaystyle \int {\frac {dx}{x(\ln x)^{n))}=-{\frac {1}{(n-1)(\ln x)^{n-1))}\qquad {\mbox{(for ))n\neq 1{\mbox{)))}$
${\displaystyle \int \ln(x^{2}+a^{2})\,dx=x\ln(x^{2}+a^{2})-2x+2a\tan ^{-1}{\frac {x}{a))}$
${\displaystyle \int {\frac {x}{x^{2}+a^{2))}\ln(x^{2}+a^{2})\,dx={\frac {1}{4))\ln ^{2}(x^{2}+a^{2})}$

## Integrals involving logarithmic and trigonometric functions

${\displaystyle \int \sin(\ln x)\,dx={\frac {x}{2))(\sin(\ln x)-\cos(\ln x))}$
${\displaystyle \int \cos(\ln x)\,dx={\frac {x}{2))(\sin(\ln x)+\cos(\ln x))}$

## Integrals involving logarithmic and exponential functions

${\displaystyle \int e^{x}\left(x\ln x-x-{\frac {1}{x))\right)\,dx=e^{x}(x\ln x-x-\ln x)}$
${\displaystyle \int {\frac {1}{e^{x))}\left({\frac {1}{x))-\ln x\right)\,dx={\frac {\ln x}{e^{x))))$
${\displaystyle \int e^{x}\left({\frac {1}{\ln x))-{\frac {1}{x(\ln x)^{2))}\right)\,dx={\frac {e^{x)){\ln x))}$

## n consecutive integrations

For ${\displaystyle n}$ consecutive integrations, the formula

${\displaystyle \int \ln x\,dx=x(\ln x-1)+C_{0))$

generalizes to

${\displaystyle \int \dotsi \int \ln x\,dx\dotsm dx={\frac {x^{n)){n!))\left(\ln \,x-\sum _{k=1}^{n}{\frac {1}{k))\right)+\sum _{k=0}^{n-1}C_{k}{\frac {x^{k)){k!))}$